IDENTIFICATION OF NON-BLOODSUCKING FLIES ON PIG FARM IN BALI - Xavier, Alice Viria Cordeiro da Costa; Dwinata, I Made; Oka, Ida Bagus Made (Buletin Veteriner Udayana, 2022)
Flies are ectoparasites that act as vectors of disease and their existence greatly affects the health of pigs. The purpose of this study was to identify the types and fluctuations in the number of flies that do not suck blood in pig farms in Badung Regency and Denpasar City. The fly collection was carried out on a semi-intensive pig farm with a period of every week for 3 months. In this study, flies were caught using fly paper glue and sweeping net and then euthanized with 70% alcohol. The data obtained were presented descriptively and analyzed using the Wilcoxon test. The identification results showed that the type of non-blood-sucking flies found in pig farms in Badung Regency and Denpasar City was Musca sp. as many as 2,383 tails (96.99%), Lucilia sp . as 56 tails (2.28%) and Fannia sp. as 18 tails (0.73%). During the 12 weeks of observation, fluctuations occurred with the highest decrease in fly population in the 3 rd week (November) and 10 th (January) while the increase occurred in the 5 th week (December) to the 9 th week (January). The number of fly population found in the Denpasar pig farm is 1,464 larger, which is largerthan the population in the pig farm in Badung Regency 993 tails.